Mapping of the extracellular RBP4 ligand binding domain on the RBPR2 receptor for Vitamin A transport - Radhakrishnan, Rakesh; Leung, Matthias; Solanki, Ashish K.; Lobo, Glenn P. (Frontiers in Cell and Developmental Biology, 2023)
The distribution of dietary vitamin A/all-trans retinol/ROL throughout the body is critical for maintaining retinoid function in peripheral tissues and for retinoid delivery to the eye in the support of visual function. In the circulation, all-trans-retinol bound to the RBP4 protein is transported and sequestered into target tissues for long-term storage. Two membrane receptors that facilitate all-trans retinol uptake from RBP4 have been proposed. While it is well established that the membrane receptor, STRA6, binds to circulatory RBP4 for ROL transport into the eye, the second vitamin A receptor, RBPR2, which is expressed in non-ocular tissues, is less characterized. Based on the structural homology between these two RBP4 receptors, published literature, and from our recent work in Rbpr2−/− deficient mice, we hypothesized that RBPR2 might also have high-binding affinity for RBP4 and this mechanism facilitates ROL transport. Herein, we aimed to elucidate the membrane topology and putative RBP4 binding residues on RBPR2 to understand its physiological function for retinoid homeostasis. Using in silico analysis and site-directed mutagenesis, we identified a potential RBP4 binding domain on RBPR2. We employed an in vitro cell-based system and confirmed that mutations of these residues on RBPR2 affected its binding to exogenous RBP4 and subsequently vitamin A uptake. Using Surface Plasmon Resonance assays, we analyzed both the binding affinities and kinetic parameters of wild-type RBPR2 and individual mutants affecting the RBPR2-RBP4 binding domain with its physiological ligand RBP4. These studies not only revealed a putative RBP4 binding domain on RBPR2 but also provided new structural, biochemical, and critical information on its proposed role in RBP4 binding for ROL transport and retinoid homeostasis.